Toward a Delaware Common Law of Closely Held Corporations - Robert A. Ragazzo (Washington University Law Quarterly, 1999)
Part I of this Article examines the national law on shareholder rights and obligations in closely held corporations. It will focus on the types of majority shareholder misconduct that have been thought sufficient to justify judicial intervention in the close corporation context. Part II examines the limited Delaware case law on closely held corporations. A close analysis of Nixon reveals that, although the court’s refusal to create special rules for closely held corporations is broadly stated, Nixon did not involve egregious misconduct by a controlling shareholder. Indeed, the specific result in Nixon might well have been reached in jurisdictions that do impose special obligations on shareholders in closely held corporations. There is, therefore, some reason to doubt that the Delaware courts will allow oppression by a controlling party in a case where the problem is squarely presented. Part III explores the extent to which the Delaware law applicable to corporations generally, including publicly held corporations, provides protection for minority shareholders in closely held corporations. In particular, controlling shareholders in all corporations have a duty of entire fairness when engaging in self-dealing transactions. Delaware, despite its general enabling philosophy, has applied the entire fairness test rigorously to protect the rights of minority shareholders. Part III argues that the Delaware entire fairness test provides a rubric that may be used to deal with most, if not all, of the special situations in which other states have provided remedies to minority shareholders in closely held corporations. In Part IV, the Article concludes that, when confronted with appropriate cases, there is reason to believe that Delaware law in the close corporation context will turn out to be similar to that of the rest of the nation.
Keywords: Close corporations -- Delaware; Stockholders -- Delaware; Fiduciary responsibility -- Delaware; Corporation law